Format Politik Pendidikan Pesantren Indonesia dari Masa ke Masa - Fadli, Muhammad Ulfi; Hidayat, Nur Kholis (Jurnal Ilmiah Citra Ilmu, 2023)
Formal education that has experienced a lot of progress and various variations cannot be separated from pesantren. Pesantren itself has been active in Indonesia for 300 to 400 years. The presence of pesantren is felt to be able to participate in educating the nation's life. To find out how big the role of politics in pessantren education is, we must know the journey from time to time. This research aims to describe the journey of the pesantren from time to time in the era of the Indonesian government. The method used in this research is to use literature review by collecting various writings, both journals, books, and other things that are relevant to this research. The results of this study are that pesantren have experienced various advances, especially in terms of quantity in each region. The underlying thing is the support from the government for the existence of pesantren. Every period in the government has different policies related to pesantren. And the policies made by the government have a great influence on the progress of education in pesantren. So it can be said that pesantren cannot develop and advance without the support of the government.